L2 hz2 z1l2 h g hx2 x1 l b g hx2 x1 l l2 hg2

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Anm Hx L then Aab ' Hx 'L = ÅÅÅÅÅÅÅÅÅÅÅÅa ÅÅÅÅÅÅÅÅÅÅÅÅÅb Amn Hx L = - ÅÅÅÅÅÅÅÅÅÅÅÅa ÅÅÅÅÅÅÅÅÅÅÅÅÅb Anm Hx L = - A ba ' Hx 'L ∑ x' ∑ x' ∑ x' ∑ x' n m ∑ x m ∑ xn ∑ x m ∑ xn HbL if Smn Hx L = Snm Hx L then Sab ' Hx 'L = ÅÅÅÅÅÅÅÅÅÅÅÅÅaÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ Smn Hx L = ÅÅÅÅÅÅÅÅÅÅÅÅa ÅÅÅÅÅÅÅÅÅÅÅÅÅb Snm Hx L = S ba ' Hx 'L ÅÅÅ ÅÅÅÅ ÅÅÅ ∑ x' ∑ x'b ∑ x' ∑ x' ∑ xa ∑ x' n Hx 'L = ÅÅÅÅÅÅÅÅÅÅÅÅÅm ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ T ÅÅÅ ∑ x' ∑ x b Hx L b a b a HcL if T and S are tensors then their components will satisfy T ' Therefore aT ' n m n m HbL Hx2 ' - x1 'L2 + Hy2 ' - y1 'L2 + Hz2 ' - z1 'L2 - Hx2 ' - x1 'L2 = H g Hx2 - x1L - b g Hx2 - x1L L2 + Hy2 - y1 L2 + Hz2 - z1L2 - H g Hx2 - x1 L - b g Hx2 - x1 L L2 = Hg2 - b2 g2L Hx2 - x1 L2 + Hy2 - y1 L2 + Hz2 - z1L2 - Hg2 - b2 g2L Hx2 - x1 L2 = Hx2 - x1 L2 + Hy2 - y1L2 + Hz2 - z1 L2 - Hx2 - x1 L2 x1 ' = cosh HuL x1 - sinh HuL x1 , y1 ' = y1 , z1 ' = z1 , x1 ' =...
View Full Document

This document was uploaded on 03/17/2014 for the course PHYSICS 600 at Purdue University.

Ask a homework question - tutors are online